What makes mothers feel competent? The relationship between parental reflective functioning, attachment style, parental competence, and stress - Szabó Brigitta; Miklósi Mónika; Futó Judit (Psihologija)
Adolescence is a time of changes; nevertheless, the mental health of adolescents’ parents receives little attention. This study aimed to explore the relationship between parental mentalizing, attachment style, parental sense of competence, and stress among mothers of adolescents. One hundred eighty-six mothers completed validated questionnaires measuring these constructs. We conducted a moderated mediation analysis with maternal attachment style as the independent variable. The dimensions of parental sense of competence efficacy and satisfaction were chosen as the dependent variables, and stress was the moderator. The mediator was the certainty about the mental states (CMS) aspect of parental mentalizing. CMS mediated the relationships between dismissing attachment style and both – efficacy and satisfaction at low-stress levels. Our results suggest that in the case of the dismissing attachment style, besides the attachment style itself, mentalizing and stress levels are also important predictors of the parental sense of competence among mothers of adolescents.